THE NARRATION ANALYSIS OF ‘ABBÂD B. YA‘QÛB AS A SYIAH RÂFIḌAH NARRATOR IN THE MAIN HADITH BOOK OF SUNNI - Amrulloh Amrulloh (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
Many scholars, both Muslim and Western, modern and contemporary, draw erroneous conclusions about the differences in theological flow in the context of the narration of hadith. One of the most crucial wrong conclusions is that the validity of the hadith is questioned because of ideological bias and political interest bias in the narration of the hadith. Whereas, a narrator widely labeled “Shafi’ah Rafi’ah”, an ideology that is claimed to be “extreme bid’ah” (al-ghuluw fi al-bid‘ah) by the Sunnis, namely ʻAbbâd b. Ya’qûb (w. 250 H), adorns many books of Sunni’s main hadith book. By applying the descriptive-analytical method and jarḥ wa ta‘dîl approach, the author is interested in exposing evidence that ‘Abbâd b. Ya‘qûb is a Shî’ah-Râfiḍah. The author is also interested in exploring the existence of ʻAbbâd in the Sunni main hadith books and analyzing the value of the hadith narrated by ‘Abbâd and the substance of the hadith narrated by ʻAbbâd in the books of the Sunni main hadith. This study proves that ‘Abbâd b. Ya‘qûb was a Hadith narrator of Syiah-Râfiḍah ideological. However, the existence of the ‘Abbâd as narrators calculated in the compilation Sunni’s Hadith main books (ummahât kutub al-ḥadîth) cannot be negated